Current Status of Sarcopenia in the Disabled Elderly of Chinese Communities in Shanghai: Based on the Updated EWGSOP Consensus for Sarcopenia - Fang, Qing; Zhu, Guoying; Huang, Jianwei; Pan, Shayi; Fang, Minyan; Li, Qiuting; Yin, Qin; Liu, Xiaoqing; Tang, Qingya; Huang, Dongping; Liu, Jingmin (Frontiers in Medicine, 2020)
Our study aimed to investigate the prevalence and associated factors of sarcopenia in the disabled elderly in communities of Shanghai, China. A cross-sectional study was conducted in 2018. 572 participants (60 years) were recruited through cluster sampling from Putuo District of Shanghai. Sarcopenia was defined according to the updated consensus of the European Sarcoma Working Group in 2019. The sarcopenia, depression, nutrition status and physical activity were assessed by using SARC-F, Short Version of Center for Epidemiological Studies Depression Scale (CES-D-10), and Mini Nutritional Assessment-Short form (MNA-SF), respectively. Our results showed the prevalence of sarcopenia was 0.5%, but the prevalence of low handgrip strength was 37.2% (male, 5.5%; female, 39.1%). The modified Poisson regression model was used to evaluate the relationship among related variables and low handgrip strength. The risk for low handgrip strength was higher in the physical disability subjects than in the visual disability ones (aPR: 1.69, 95% CI: 1.88-2.42). Depressive symptoms (aPR: 1.31, 95% CI: 1.04-1.62) and PASE score (aPR: 0.99, 95% CI: 0.99-1.00) were independently associated with low handgrip strength. In summary, the prevalence of EWGSOP2-defined sarcopenia is low and the prevalence of declined muscle strength is high in the disabled elderly. The elderly with physical disability has a higher prevalence of low hand handgrip strength than those with visual disability. More studies with large sample size and longitudinal follow-up are needed to confirm our findings.